Nicaragua - Delgado Rocha, Byron Antonio (Universidad de Costa Rica, 2020)
This article analyzes the results of a curricular investigation carried out in Nicaragua, in the period 2018-2019 and in the regular modality, provided by the Nicaraguan Ministry of Education and managed by the teacher training schools, which grants the title of Primary Education Teacher and that is attended simultaneously with the secondary from the ninth grade. The purpose was to contrast what the evidence suggests is necessary to know and be able to do in order to teach early grade literacy (EGL), and the content of the primary education teacher training curriculum. The methodology followed a qualitative approach based on curriculum mapping, interviews with teacher trainers and teachers-in-training, and classroom observations of subjects related to child development, EGL content, and assessment of learning. Among its main findings, it is worth noting that there is a partial and insufficient alignment of the content of the curriculum with the evidence on effective instruction of this subject. Gaps were identified in content, course bibliographies and time spent on teaching with respect to actual training needs. It was also found that in many classes what is prescribed is different from what is implemented due to the context and individual and institutional experiences of the teacher trainers. The research concludes that key issues critical to effective EGL instruction are not included in the curriculum, evidence is not being considered in the teacher training program, and insufficient time is being given to teaching and practice on instruction.